PENGEMBANGAN PERMAINAN OUTBOUND UNTUK PENINGKATAN KETERAMPILAN GERAK DASAR SISWA PAUD SAYANG ANAK KECAMATAN SUKAMULIA KABUPATEN LOMBOK TIMUR - Muslihan Muslihan (JCE (Journal of Childhood Education), 2017)
The problem in this research is "What is the outbound game development model to encourage the improvement of basic movement skill of Sayang Anak Early Childhood Education (PAUD) Sukamulia subdistrict, East Lombok, Academic Year 2005/2016?". The purpose of this research is to produce outbound game development model to encourage the improvement of basic movement skills of PAUD Sukamulia sub-district, East Lombok academic year 2015/2016 in physical motor learning to develop various aspects of learning and increase the physical activities of PAUD students. This research is a development research. The product development procedures include product analysis to be created, initial product development, expert validation and revision, small group trials and revision, large group trials and end products. Data collection methods are through questionnaires obtained from expert evaluation, observation and interview. Data analysis technique used is descriptive percentage. Based on the research data, it is concluded that the development of outbound games could encourage the improvement of basic movement skills effectively and in accordance with the characteristics of students so that it can be used in physical education learning in early childhood